Elevational environmental stress modulating species cohabitation in nests of a social insect - Viana‐Junior, Arleu B.; Mitraud, Paola; Dáttilo, Wesley; DeSouza, Og; Neves, Frederico (Ecological entomology, 2021)
Termite nests may offer shelter to a number of species, alleviating the effects of environmental harshness. Certain elevational gradients provide variation on edaphoclimatic features, possibly generating harsh environmental conditions and boosting the number of immigrants seeking shelter within termitaria. Therefore, it is expected that metrics describing the community of termitaria cohabitants would correlate with elevation. To test this hypothesis, we surveyed the termitophiles inhabiting 20 nests of Nasutitermes coxipoensis along an elevational gradient in a tropical mountain in Brazil. We assessed the richness, abundance, and composition (β‐diversity) of termite nests' cohabitants, testing nest volume and elevational position as explanatory covariates. We found a positive correlation between the elevation at which termitaria were located and the richness and abundance of cohabiting termitophiles. Additionally, no correlation was found between elevational distance and dissimilarity of cohabitant communities between termitaria. Hence, the understanding that termitaria work as an ‘oasis’ of favorable microclimate is reinforced by our findings that the composition changed but was not correlated to elevation. In short, environmental harshness boosts the establishment of distinct species of termitophiles in termitaria and it does so regardless of the invading species identity. This study showed how the elevational gradient of a tropical mountain affects the cohabitants in termite nests. We found a positive correlation between the elevation of termitaria and termitophiles diversity. However, no correlation was found between elevational distance and dissimilarity of cohabitant communities between termitaria. Termitaria provide shelter and suitable microclimates for a non‐specialized variety of organisms in a harsh environment.